Gobierno y casinos. El origen de la riqueza de Abelardo L. Rodríguez - Almaraz, Araceli (Frontera Norte, 2017)
José Alfredo Gómez Estrada, 2a. ed., México, Instituto Mora y Universidad Autónoma de Baja California, 2007.